2019
DOI: 10.2174/1386207322666190125150557
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Vitamin D Receptor Gene Polymorphism with Lung Cancer Risk: An Update Meta-analysis

Abstract: The association between vitamin D receptor (VDR) genetic polymorphism and lung cancer risk has been evaluated by the previous meta-analyses. Due to the emergence of novel studies and inappropriate inclusion of overlapping populations, an updated meta-analysis on recent evidences is necessarily needed. We comprehensively searched databases of PubMed, Web of Science and Chinese National Knowledge Infrastructure and finally obtained 7 eligible studies according to the inclusion criteria. Four positions on VDR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The results showed that Bsm1 and Cdx2 polymorphisms were protective factors for avoiding lung cancer incidence, while T allele and TT genotype of Taq1 were risk factors for lung cancer susceptibility. Our results were partly consistent with previous meta-analysis studies conducted by Yu et al (2018), which indicated that the Bsm1 A allele was negatively related to the lung cancer risk and the T allele carriers were at increased risk of lung cancer, and by Li et al (2019), which suggested that Bsm1, Taq1, and Cdx-2 polymorphisms may contribute to lung cancer susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that Bsm1 and Cdx2 polymorphisms were protective factors for avoiding lung cancer incidence, while T allele and TT genotype of Taq1 were risk factors for lung cancer susceptibility. Our results were partly consistent with previous meta-analysis studies conducted by Yu et al (2018), which indicated that the Bsm1 A allele was negatively related to the lung cancer risk and the T allele carriers were at increased risk of lung cancer, and by Li et al (2019), which suggested that Bsm1, Taq1, and Cdx-2 polymorphisms may contribute to lung cancer susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, just 3 previous researches have investigated the effect of VDR genetic polymorphism in relation to LC risk. [39][40][41] In this present study, we identified 3 locus in VDR genes have significant association with LC. Currently, compared with the previous, there are various advantages in our study, more gene loci were included in analysis, especially to Cdx-2, which is the first gene loci included in this meta-analysis, more databases were retrieved (Pubmed, PMC, Embase, Cochrane library, Web of Science and CNKI), more studies with better quality were selected for analysis, the relationship between polymorphism of candidate gene locus and lung cancer susceptibility was analyzed under 5 genetic models, stratified analysis was further conducted by ethnicity and larger sample size increased the statistical capacity.…”
Section: Discussionsupporting
confidence: 55%
“…In this meta-analysis, we comprehensively assessed 4 candidate SNPs (Bsm1, Apa1, Taq1, Cdx-2) of VDR gene for association with LC susceptibility from 9 selected studies, and we found many differences between the results of this study and previous studies. [39][40][41] Previous studies have shown that Apa1 and Bsm1 were associated with LC risk in overall populations, Caucasians and Asians in some genetic models. However, according to our study, all genetic models of Apa1 failed to find correlation with LC incidence both in overall and stratified analysis, no association was found between Bsm1 and susceptibility to LC in Caucasians although it could reduce the risk of LC in overall populations and Asians under all 5 genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that polymorphisms in the VDR gene are associated with a greater risk of lung cancer compared to those without such variations. Moreover, the researchers found that the risk of lung cancer increased with the number of VDR gene variations present in an individual [ 78 ]. This provides evidence that VDR gene variations may be an important factor in lung cancer risk.…”
Section: Vitamin D Receptor Gene Variation and Lung Cancer Riskmentioning
confidence: 99%